VISUM ET REPERTUM: A MEDICOLEGAL REPORT AS A COMBINATION OF MEDICAL KNOWLEDGE AND SKILL WITH LEGAL JURISDICTION - Winda Trijayanthi Utama (JUKE Unila, 2014)
Visum et Repertum (VeR) is a medicolegal report which is made by a doctor in his capacity as an expert based on the examination of the person or people suspected. Due to an official request from an authorized law officer of what that were seen and found on the examination object while remembering the doctor’s oath. A VeR role as one of the valid evidence for proof of criminal cases against human health and life. Actually there is no reason for a doctor to refuse to make VeR, because this is meant to fulfill the formulation offence in Indonesia’s Penal Code (KUHP). A VeR basically is a compilation and its interpretation of a forensic medical examination as well as a physical examination on a routine medical examination. A VeR should not only fulfill the writing standard, but must also fulfill several terms and conditions for a court system. A good quality VeR has a certain structure and standard. A VeR written down with five main compositions, as opening parts (head of letter and sentence) “PRO JUSTICIA”, introductory data (data on requesting police institution, brief description on personal victim profile, identity of examinating doctor), report on factual findings (whole body character, related sign and symptoms, causal factor identified from victim), medicolegal conclusion (interpretation of report on factual finding in correlation with jurisdiction) and closing pledge statement. [JuKe Unila 2014; 4(8):269-275]